Magnetic solid phase extraction as a nonchromatographic method for the quantification of ultratrace inorganic arsenic in rice by inductively coupled plasma-optical emission spectrometry (ICP OES). (30th June 2023) - da Silva, Francisco L.F.; Lima, Francisco E.H.; Andrade Neto, Davino M.; de Menezes, Fernando L.; Fechine, Lillian M.U.D.; Akhdhar, Abdullah; Ribeiro, Livia P.D.; Nogueira, Ana R.A.; Fechine, Pierre B.A.; Lopes, Gisele S.; Matos, Wladiana O.
Graphical abstract: Highlights: A method based on MSPE was developed for iAs analysis in rice by ICP OES. It is possible to quantify tAs at µg kg −1 levels by ICP OES. The use of MSPE with nanomaterials improves As preconcentration by 20-fold. The developed method has higher sensitivity for tAs and iAs than HPLC-ICP-MS. An interaction mechanism between the analyte and the nanomaterial was proposed. Abstract: An alternative analytical method was developed for the quantification of inorganic arsenic (iAs) in rice by ICP OES. Iron nanoparticles modified with an organophosphorus compound were used as the solid phase for MSPE of iAs from the plant matrix. The MSPE procedure was performed using 4 mL of a buffer solution with pH 4.0, 20 mg of the nanomaterial, and a 15-min extraction time. The total As (tAs) by ICP OES was also quantified using the same MSPE procedure after solubilization of the samples by a block digester. The accuracy of tAs and iAs quantification was verified using CRM NIST 1568b (97 % and 101 % recovery, respectively). The precision (RSD < 15 %) and LOD and LOQ (1.08 and 3.70 µg kg −1, respectively) of the proposed method were satisfactory. The rice samples had tAs contents between 0.090 and 0.295 mg kg −1 and iAs mass fractions between 0.055 and 0.109 mg kg −1 .